The external side of Europe's great economic transformation: International trade in services - Lucian Cernat; Carmen Díaz-Mora; Oscar Guinea (European Centre for International Political Economy (ECIPE), 2024)
Europe's digital transition is starting to bear fruits. Europe's economic landscape is becoming increasingly digital, with sectors like information and communication technology (ICT) capturing a growing share of EU GDP. This Policy Brief examines the impact of these economic shifts on Europe's trade profile and the policies that the EU can pursue to support this transformation.
Keywords: 330